EFEKTIVITAS BRAND IMAGE, BRAND TRUST, HARGA, KUALITAS LAYANAN DAN KEPUASAN TERHADAP KEPUTUSAN PEMBELIAN AIR MINERAL KEMASAN “SANTRI” PADA SANTRI PUTRA DAN PUTRI PONDOK PESANTREN DARUL FALAH RAMBAN KULON BONDOWOSO - Usman Usman (KASBANA, 2021)
One of the company’s decisions that are important in competing product strategy is marketing activities. This study aims to empirically test the variables of the research, includes the question of whether there are any influences of the Brand Image (X1), Brand Trust (X2), Price (X3), Service Quality (X4) and Satisfaction (X5) of the Purchase Decision (Y). The samples in this study are taken by using aAccidental Sampling. They are 93 people from the population of 950; they are student in the Darul Falah Ramban Kulon Bondowoso Islamic Boarding School. The analyzes are performed by using the multiple linear regression analysis. Furthemore, the testing of the hypothesis is done with the software of Statistical Package for the Sciences (SPSS) in 18 version. The results of the analysis show that the Brand Image has no effect on Purchasing Decisions with the results of tcount 0.142 <ttable 1.6614 significance value 0.887> 0.05. Brand Image has no significant effect on Purchasing Decisions with a tcount of 1.842> ttable 1.6614 significance of 0.069> 0.05. Price variable shows the results of a significant effect on Purchasing Decisions with a value of tcount 2.074> ttable 1.6614 significance 0.041 <0.05. The next result shows that service quality has a significant effect on purchasing decisions with a value of tcount 3.852> ttable 1.6614 and significance 0.000 and satisfaction variable has a significant effect on purchasing decisions with a tcount of 5.722> ttable 1.6614 significance 0.000. Simultaneously brand image, brand trust, price, service quality and satisfaction have a significant effect on purchasing decisions